Application of the Model View Controller Concept for the Academic Information System at PKBM Nola - Moch Farhan; Setiawan, Eman (Informatics and Software Engineering, 2023)
The Academic Information System (SIA) is important in managing academic data, including processing and reporting report cards, in non-formal educational institutions such as PKBM Nola. This research aims to apply the Model-View-Controller (MVC) concept in the Academic Report Card Information System at PKBM Nola to increase efficiency and accuracy in processing academic data. This study uses a structured software development approach in which the SIA Raport system design is based on the MVC concept. The model manages academic data, including student information, subjects, and grades. View is responsible for displaying the user interface that allows users to view and manipulate academic data. The controller is a liaison between the Model and View, managing data flow and maintaining data integrity. By applying the MVC concept in the Academic Reports Information System at PKBM Nola, institutions can benefit from processing academic data, increasing efficiency, and providing accurate information to relevant stakeholders. This research provides a foundation for developing a better academic information system in other non-formal education institutions, emphasizing systematic segregation of duties and responsibilities through the MVC concept.   Sistem Informasi Akademik (SIA) memiliki peran penting dalam pengelolaan data akademik, termasuk pengolahan dan pelaporan raport, di lembaga pendidikan nonformal seperti PKBM Nola. Tujuan dari penelitian ini adalah untuk menerapkan konsep Model-View-Controller (MVC) dalam Sistem Informasi Akademik Raport di PKBM Nola guna meningkatkan efisiensi dan akurasi dalam proses pengolahan data akademik. Penelitian ini menggunakan pendekatan pengembangan perangkat lunak yang terstruktur, di mana desain sistem SIA Raport didasarkan pada konsep MVC. Model berfungsi untuk mengelola data akademik, termasuk informasi siswa, mata pelajaran, dan nilai-nilai. View bertanggung jawab untuk tampilan antarmuka pengguna yang memungkinkan pengguna untuk melihat dan memanipulasi data akademik. Controller berperan sebagai penghubung antara Model dan View, mengatur aliran data dan menjaga integritas data. Melalui penerapan konsep MVC dalam Sistem Informasi Akademik Raport di PKBM Nola, lembaga dapat memperoleh manfaat signifikan dalam pengolahan data akademik, meningkatkan efisiensi, dan memberikan informasi yang akurat kepada stakeholder terkait. Penelitian ini memberikan landasan untuk pengembangan sistem informasi akademik yang lebih baik di lembaga pendidikan nonformal lainnya, dengan penekanan pada pemisahan tugas dan tanggung jawab sistematis melalui konsep MVC.